In vitro effect of agomelatine on spontaneous and oxytocin-induced contractions in the rat myometrium - Kacar, E.; Ercan, Z.; Serhatlioglu, I; Kelestimur, H. (Wiley-Blackwell, 2015)
[Abstract Not Available]